The Capacity to Evaluate : Why Countries Need It - Morra-Imas, Linda (World Bank, Washington, DC, 2012)
Evaluation skills are central to effective development work. Evaluation captures real results, leads to feedback and learning, and identifies areas where more capacity is needed. It is also an essential tool for making mid-course corrections in ongoing programs, developing appropriate indicators, tracking an individual's or organization's capacity to deliver on its mandate, and guiding the design of future programming. Donors now expect countries to be full partners in the development process, which means that they need to have the capacity to evaluate their own progress and to use the findings to continuously improve their performance. The evidence suggests that these changes can potentially have a transformative effect on governance and make poverty reduction efforts dramatically more effective. The World Bank, in partnership with Carleton University in Ottawa, is currently providing evaluation capacity development through its International Program for Development Evaluation Training (IPDET), which has already trained more than 850 practitioners from 100 countries.